2020
DOI: 10.1038/s41598-020-68548-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of induced systemic resistance determinants from Bacillus simplex Sneb545 against Heterodera glycines

Abstract: Heterodera glycines is one of the most destructive pathogens of soybean. Soybean seeds coated with Bacillus simplex Sneb545 have shown resistance to H. glycines as a result of induced systemic resistance (ISR) in the plants. In this study, we aimed to identify the resistance-inducing determinants from this B. simplex strain. Combining the ISR bioassay, six ISR-active compounds were isolated from a culture of B. simplex Sneb545 using organic solvent gradient extraction, silica gel column chromatography, Sephade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Similarly, B. velezensis strain FZB42 produces bacilysin, bacillaene, and diffcidin which suppress fire blight disease in plants [8]. Recently, it was reported that B. subtilis SL18r and B. simplex Sneb545 elicit induce systemic resistance in plants against Botrytis cinerea and Heterodera glycines, respectively [9,10]. Furthermore, volatile organic compounds such as acetoin and 2,3-butanediol have also been reported to trigger systemic resistance in plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, B. velezensis strain FZB42 produces bacilysin, bacillaene, and diffcidin which suppress fire blight disease in plants [8]. Recently, it was reported that B. subtilis SL18r and B. simplex Sneb545 elicit induce systemic resistance in plants against Botrytis cinerea and Heterodera glycines, respectively [9,10]. Furthermore, volatile organic compounds such as acetoin and 2,3-butanediol have also been reported to trigger systemic resistance in plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ten known compounds, uracil (2) ( Xing et al, 2020 ), cyclo-(L-Pro-L-Tyr) (3) ( Jayatilake et al, 1996 ), bis-(2-ethylhexyl) terephthalate (4) ( Firdovsi et al, 2007 ), 4-hydroxybenzaldehyde (5) ( Shataer et al, 2020 ), 2-phenylethanol (6) ( Guerrini et al, 2011 ), 4-hydroxyphenethyl-alcohol (7) ( Wei et al, 2013 ), estigmast-4-en-6β-ol-3-ona (8) ( Correia et al, 2003 ), ergosterol (9) ( Zhang et al, 2002 ), ergosterol peroxide (10) ( Hybelbauerová et al, 2008 ), and cerevisterol (11) ( Kang et al, 2017 ) were also isolated from Pseudofusicoccum sp. J003.…”
Section: Resultsmentioning
confidence: 99%
“…atrofaciens (McCulloch). Endophytic microorganisms of grain are considered as one of the most important resistance-inducing determinants of the plant resistance to the phytopathogen [23]. Considering this, grains of Podolyanka wheat variety were chosen for the search of endophytic bacteria with PGPT and antagonistic activity against phytopathogenic bacteria.…”
Section: Resultsmentioning
confidence: 99%